Regional and global monetary cooperation - Mario Lamberte; Peter J. Morgan (Asian Development Bank Institute (ADBI), 2012)
The increasing occurrence of national, regional, and global financial crises, together with their rising costs and complexity, have increased calls for greater regional and global monetary cooperation. This is particularly necessary in light of volatile capital flow movements that can quickly transmit crisis developments in individual countries to other countries around the world. Global financial safety nets (GFSNs) are one important area for monetary cooperation. This paper reviews the current situation of regional and global monetary cooperation, focusing on financial safety nets, with a view toward developing recommendations for more effective cooperation, especially between the International Monetary Fund (IMF) and regional financial arrangements (RFAs). A GFSN should have adequate resources to deal with multiple crises, should be capable of rapid and flexible response, and should not be encumbered by historical impediments such as the IMF stigma that would limit its acceptance by recipient countries. Oversight of a GFSN needs to be based on cooperation between global and regional forums, for example, the G20 and ASEAN+3 or East Asia Summit (EAS). Such a GFSN should include the IMF and RFAs at a minimum, and it is highly recommended to find ways to include central banks as providers of swap lines and multilateral banks as well. The basic principles governing the cooperation of IMF and RFAs include rigorous and even-handed surveillance; respect of independence and decision-making processes of each institution and regional specificities; ongoing collaboration as a way to build regional capacity for crisis prevention; open sharing of information and joint missions where necessary; specialization based on comparative advantage; consistency of lending conditions and conditionality, although with flexibility; respect of the IMF as preferred creditor; subsidiarity; avoidance of moral hazard; and transparency.
Keywords: F33; F34; F36; F53; F55; 330; monetary cooperation; regional monetary cooperation; global monetary cooperation; regional financial arrangements; financial safety nets; global financial crises; Geldpolitik; Internationale Wirtschaftspolitik; IWF-Kredit; Internationale Finanzhilfe; ASEAN-Staaten; Asien